Oral Language Proficiency Level of International Business Process Outsourcing Agents - Bulilan, Ramil S.; Ponte, Shaun James T. (JPAIR Multidisciplinary Research, 2018)
Oral English language proficiency is an important skill every call center agent must possess. Towards this end, this study sampled 125 call center agents of Sykes in Cebu City, Philippines primarily to determine their level of proficiency in oral discourse. A descriptive-quantitative design was pursued wherein respondents were assessed using the said industry’s standardized instrument that measured on their pronunciation, stress, and intonation; language accuracy, and vocabulary range; discourse and strategic competency; and, interactive fluency and sociolinguistics. It also specifically sought answers on their gender, highest educational attainment, school attended, and place of origin. We presumed that their highest educational attainment and gender had influenced their oral language proficiency level. Results revealed they were modest users which mean that they are non-native-speaker-like agents. They have partial command of the language. Statistical tests revealed no significant difference and relationship, respectively, on respondents’ oral proficiency level in terms of their gender and highest educational achievement. These imply that whether male or female, and finished college or not, their oral proficiency level is not affected. In other words, gender and college achievement are not the factors towards their oral proficiency level. Nevertheless, call center agents of Sykes to need to improve their oral language skills for them to retain employment.